Barriers to Early Breast Cancer Diagnosis in Sudanese Women Before the War - Elamin HES; Elamin HES; Abd El-Raheem GOH; Noma M (Breast Cancer: Targets and Therapy, 2025)
Hana Eltayeb Salih Elamin,1 Hind Eltayeb Salih Elamin,2 Ghada Omer Hamad Abd El-Raheem,3 Mounkaila Noma1 1High Diploma in Research Methodology and Biostatistics, University of Medical Sciences and Technology UMST, Khartoum City, Khartoum State, Sudan; 2Clinics, Abu Dhabi Telemedicine Centre, Abu Dhabi, United Arab Emirates; 3Pharmacy, Soba University Hospital, Khartoum City, Khartoum State, SudanCorrespondence: Hana Eltayeb Salih Elamin, Email hana_elamin@outlook.comBackground: Breast cancer in African women is characterized by early onset, late presentation, and consequently poor prognosis. The reason for the late presentation was the delay by patients, due to ignorance, superstition, a skeptical attitude towards western medicine, and dependency on traditional medicine.Objective: The aim of our study was to assess the factors of late presentation at Khartoum Oncology hospital of women suffering from breast cancer.Methods: A hospital based cross-sectional study was implemented to assess the causes related to late presentation of women with breast cancer. Statistical analysis tests done to assess associations among variables were performed through chi2. A multi-nominal regression analysis assessed the factors associated to late presentation. All statistical tests were considered significant when p< 0.05.Results: 250 females with breast cancer were studied, their age ranged between 22 years and 77 years with a median of 50 years. Barriers to early presentation were the duration of the condition before presentation (p=0.003) and most importantly the lack of education (p=0.048). As well as having low financial status (p= 0.045) and favouring alternative treatments such as herbal medicine (p=0.041) and Quran therapy (p=0.047). Other reasons were the fear of doctor and surgery (p=0.021) and the fear of diagnosis with a serious condition (p=0.009). Breast cancer was prevalent in all states of Sudan especially Northern state.Conclusion: Fear and seeking treatment alternatives strongly contributed to late presentation. The lack of education and the unawareness about breast self-examination (BSE) are issues needed to be addressed by authorities.Keywords: factors, late presentation, breast cancer, oncology, pathological stage